Exploring the Use of Little Cigars by Students at a Historically Black University - David H. Jolly, DrPH (Centers for Disease Control and Prevention, 2008)
IntroductionConsiderable evidence exists that little cigars are popular among African American adolescents and young adults who smoke. However, few studies have been published on the use of this tobacco product by young blacks in the United States. This research investigated little-cigar use among students at a historically black university in the southeastern United States.MethodsAs a follow-up to a survey on tobacco use among freshmen that revealed unexpectedly high rates of little-cigar use, 3 focus groups were conducted with current or former smokers of little cigars. Topics included preferred brands of little cigars, preference for little cigars over cigarettes, social contexts for smoking little cigars, perceived health risks of smoking little cigars relative to smoking cigarettes, and thoughts about quitting.ResultsFocus group participants preferred little cigars to cigarettes for various reasons, among them taste, smell, a better "buzz," social purposes, status, and perceptions that smoking little cigars is less addictive and less harmful than smoking cigarettes. Opinions on health risks varied; some participants believed that health risks can be reduced by removing the inner liner of little cigars.ConclusionUse of little cigars should be addressed in tobacco research, use prevention, and use cessation efforts, targeting students at historically black colleges and perhaps other young African Americans. Results also suggest that clear distinctions should be made among cigarettes, little cigars, and cigars, and that tobacco use prevention and cessation programs should debunk myths that little cigars are a safe alternative to cigarettes. Study findings should be confirmed and elucidated through additional research.